Experimental and Numerical Investigation on a Water-Filled Cavity Natural Convection to Find the Proper Thermal Boundary Conditions for Simulations. Issue 4 (25th February 2018) - Mahdavi, Mostafa; Sharifpur, Mohsen; Ghodsinezhad, Hadi; Meyer, Josua P.
ABSTRACT: In this study, the laminar natural convection flow inside a water-filled cavity with differentially heated vertical walls is investigated experimentally and numerically. Both of the walls are heated and cooled by two special heat exchangers that are attached to the walls and the rest are insulated. The main purpose of each test is to reach a uniform constant temperature on both of the heated and cooled walls. Early tests for an air-filled cavity showed that a uniform temperature on the walls is feasible, while a different trend was observed for a water-filled cavity with a nonuniform distribution of temperature. ANSYS FLUENT 15 employed four approaches in terms of boundary conditions for computational purposes. None of the three-dimensional (3D) and two-dimensional (2D) models of the cavity with a uniform wall temperature (the wall average temperature from the experiment) were suitable for predicting the Nusselt number. Therefore, it was essential to use the full model to properly predict the real distribution of temperature and Nusselt number on the walls. The 3D model of the cavity with a nonuniform wall temperature, which was borrowed from the experiment, also provided good results for the Nusselt number, but a measured temperature was still needed from the experiments. The 2D simulation's findings showed a weakness in properly capturing the streamlines for all ranges of Rayleigh numbers.